New Methodology of Assessing Wasted Energy in Industrial Sector: Assessing Industrial Systems contribution to Thermal Pollution - Pitis, Constantin (Journal of Environmental Science and Engineering Technology, 2013)
Thermal Pollution represents “the release into the environment of substances that are innocuous themselves but at a temperature higher than the ambient altering the physical characteristics of the air or water with which they mix” (Science Dictionary). The quantity of the heated air dumped in the atmosphere is intrinsically related to efficiency of industrial systems, processes and industries. Increasing efficiencies of industrial systems, processes and industries will directly reduce the thermal pollution. In other words, all energy savings obtained by increasing energy efficiency of industrial systems and processes (IS&P) represents avoided Thermal Pollution. To date, studies of energetic performances of industrial systems and industries have lagged behind those used in the commercial and institutional sectors due to: Variability and complexity of IS&P, Variability of material and environmental conditions, The absence of a large population of comparable data required for a regression-based approach that would enable the normalization of material and environmental conditions, and thus allow for a useful comparison of energy performance at the process level. The reluctance of industrial firms to share data on industrial processes that is often considered proprietary. Paper proposes: an energetic assessment of Thermal Pollution by using a new rating system model describing the energy efficiency of any industrial equipment, system drive or process independent of a comparison with other processes. Comparative element across an industrial sector that is traditionally used, is replaced with a theoretical goal. The rating is then solely based on how close the true energy consumption within an industrial process gets to that ideal state. Proposed methodology splits energy consumption in 2 (two) specific components: Ideal energy (EIdeal) and Energy at Risk (E@R) – that represents actually the Thermal Pollution (Th.P). By considering these two energy types Benchmark Energy Factor (BEF) can be defined. The (BEF) will enable a new approach towards energy efficiency in the industrial sector and help level the playing field for energy management reducing the waste energy and therefore Thermal Pollution. It will be demonstrated that Energy at Risk (Thermal Pollution) variation is embedded in (BEF). Once Energy at Risk (E@R) is known, it will be logical proceeding with benchmarking plants, industrial systems or/and processes assessing their capability of managing E@R (waste energy or Th.P) by focusing on in-situ testing and making educated decision towards reducing wasted heat and thermal pollution. Case studies on proposed methodology are presented at the level of equipments, industrial system drives, plants, processes, and industries. The methodology of determining the magnitude of thermal pollution is applied to a typical national industrial system by using conservation potential obtainable when Integrated Industrial System Drives (IISD) are to be used. The scope of this paper is to uncover Th.P. as new pollutant that can be included in EPA Clean Air Act making available to consultants, designers, end-users, utility programs and environmental organizations reliable criteria of reducing thermal pollution of the existing or new industrial systems or plants as part of the climate change mitigation.